2003
DOI: 10.1111/j.1741-2358.2003.00095.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Sinhalese translation of the Oral Health Impact Profile‐14 for use with older adults

Abstract: The Sinhalese translation of the OHIP-14 is a valid and reliable instrument to measure oral health related quality of life in older adults of Sri Lanka.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 7 publications
8
45
0
2
Order By: Relevance
“…The result above 0.9 obtained in our study for all 14 items of OHIP-14 (excellent internal consistency), is also confirmed by reports from other research centers. Similar results were obtained in Italy (0.90), Greece (0.90) and Sri Lanka (0.93) [16][17][18]. The results of our study were slightly better than those reported by Ostberg et al, whose results showed that internal consistency measured with Cronbach's alpha was 0.86 for 7 subscales and 0.88 for 14 separate items; similar results were published by Slade who reported high reliability (0.88) [19].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The result above 0.9 obtained in our study for all 14 items of OHIP-14 (excellent internal consistency), is also confirmed by reports from other research centers. Similar results were obtained in Italy (0.90), Greece (0.90) and Sri Lanka (0.93) [16][17][18]. The results of our study were slightly better than those reported by Ostberg et al, whose results showed that internal consistency measured with Cronbach's alpha was 0.86 for 7 subscales and 0.88 for 14 separate items; similar results were published by Slade who reported high reliability (0.88) [19].…”
Section: Discussionsupporting
confidence: 80%
“…All the inter-item correlations were positive, and none was high enough for any item to be redundant, while the item-total correlations coefficients were above the recommended threshold (0.20) for including an item in a scale, which was also confirmed by research done among Iranians [22]. The validity construction was mostly supported by the subjective criteria as in other studies [13,17,18,21,[23][24][25][26][27]. Our results only confirm previous assumptions according to which dental problems may not only be a source of pain, but may also cause emotional and physical disorders.…”
Section: Discussionsupporting
confidence: 76%
“…Culturally, some situations are still socially "acceptable" in aging groups, such as dental loss, the use of unsuitable dentures and halitosis. In certain cases, toothless people consider dental loss a normal event in aging process 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Com relação à tradução da linguagem original para a linguagem fonte, diversos métodos foram utilizados na literatura revisada, variando de uma simples tradução como a realizada por Ekanayake & Perera 14 e Kushnir et al 15 , a três traduções com tradutores que possuíam a lín-gua alvo como primeira língua 16,17 . Um estudo utilizou cinco dentistas na primeira tradução do instrumento.…”
Section: Resultsunclassified